1989
DOI: 10.1126/science.2672330
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenesis of the Polarized Epithelial Cell Phenotype

Abstract: Polarized epithelial cells play fundamental roles in the ontogeny and function of a variety of tissues and organs in mammals. The morphogenesis of a sheet of polarized epithelial cells (the trophectoderm) is the first overt sign of cellular differentiation in early embryonic development. In the adult, polarized epithelial cells line all body cavities and occur in tissues that carry out specialized vectorial transport functions of absorption and secretion. The generation of this phenotype is a multistage proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
591
0
3

Year Published

1992
1992
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,034 publications
(603 citation statements)
references
References 138 publications
9
591
0
3
Order By: Relevance
“…Tight junction formation is critical for polarized epithelial cells carrying out specific vectorial transport functions of absorption and secretion (14), and maintaining the protein and lipid differences between apical and basolateral membrane domains (15). Although we did not study tight junction formation in the present study, previous electron microscopic and freeze-fracture studies of full term human placentas have shown the presence of the tight junction (zonulae occludente and maculae occludente) structure within apical invaginations of the syncytiotrophoblastic layer (16,17), which support the concept that placental syncytiotrophoblasts are polarized epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Tight junction formation is critical for polarized epithelial cells carrying out specific vectorial transport functions of absorption and secretion (14), and maintaining the protein and lipid differences between apical and basolateral membrane domains (15). Although we did not study tight junction formation in the present study, previous electron microscopic and freeze-fracture studies of full term human placentas have shown the presence of the tight junction (zonulae occludente and maculae occludente) structure within apical invaginations of the syncytiotrophoblastic layer (16,17), which support the concept that placental syncytiotrophoblasts are polarized epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Both secretion and delivery of proteins to the plasma membrane are very much more complex in polarized cells [47][48][49]. Polarization is an issue not only for the constitutive pathway, but also for regulated secretion from both epithelial cells and, most notably, exocrine cells [20,40], as well as from some endocrine cells, including the pancreatic B cell [50].…”
Section: Protein Secretory Pathways: a General Outline Leader And Leamentioning
confidence: 99%
“…The establishment and maintenance of cell polarity requires cell-substratum attachment, formation of intercellular contacts and junctions, polarized cytoskeletal networks, and specialized membrane transport pathways (Rodriguez-Boulan and Nelson, 1989). Epithelialization would expectedly involve the reorganization of a ubiquitous expression of cell surface proteins on mesenchymal cells to a more restricted distribution in line with more specialized functions that are required for vectorial transport.…”
Section: Introductionmentioning
confidence: 99%